Effect of helium on micro-fracture strength for multi-ion-irradiated F82H by micro-tensile testing - Masami Ando; Takashi Nozawa; Ryuta Kasada; Hiroyasu Tanigawa (Nuclear Materials and Energy)
Reduced-activation ferritic-martensitic steels (RAFM) are leading candidates for application as blanket structural materials in fusion DEMO reactors. It is especially important to evaluate the effects of 14 MeV neutron irradiation on the properties of the material. However, fusion neutron irradiation facilities are not yet operational, and it is important to determine the threshold (critical point) at which helium induces changes in the properties of a typical material. This study was aimed at investigating the effect of helium on the micro-fracture strength of single-block F82H steel after multi-ion irradiation by using micro-tensile testing with notches.Fracture strength measurements were performed for unirradiated, single-ion-irradiated, and dual-ion-irradiated F82H. The fracture surface of the unirradiated F82H exhibited a large deformation by multiple active slip systems. In contrast, ion-irradiated F82H was broken with only one or two active slip systems (mainly shear deformation). Some of the specimens with low micro-fracture strengths exhibited flat surfaces with minimal deformation. The micro-fracture strength tended to increase with irradiation doses at 300–350 °C (>40 dpa), irrespective of whether helium was used or not. For ion-irradiated F82H at 300 °C and 80 dpa, the micro-fracture strengths of the single- and dual-irradiated F82H were ∼ 1700 and ∼ 2000 MPa, respectively. Moreover, the latter showed a large dispersion of micro-fracture strength, according to Weibull analysis. Based on these results, this study demonstrates the possibility of evaluating the micro-fracture strength of ion-irradiated F82H.